2012
DOI: 10.1210/en.2012-1517
|View full text |Cite
|
Sign up to set email alerts
|

The Cortisol and Androgen Pathways Cross Talk in High Temperature-Induced Masculinization: The 11β-Hydroxysteroid Dehydrogenase as a Key Enzyme

Abstract: In many ectotherm species the gonadal fate is modulated by temperature early in life [temperature-dependent sex determination (TSD)] but the transducer mechanism between temperature and gonadal differentiation is still elusive. We have recently shown that cortisol, the glucocorticoid stress-related hormone in vertebrates, is involved in the TSD process of pejerrey, Odontesthes bonariensis. Particularly, all larvae exposed to a male-producing temperature (MPT, 29 C) after hatching showed increased whole-body co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(92 citation statements)
references
References 52 publications
6
85
0
Order By: Relevance
“…In the pejerrey, cortisol interacts with the glucocorticoid response element in the promoter of the 11β-hydroxysteroid dehydrogenase type 2 (hsd11β2) gene, a key enzyme that is shared between the glucocorticoid and androgen pathways, increasing its expression. This led Fernandino et al, (2012Fernandino et al, ( , 2013 to suggest that while increased hsd11β2 expression contributes to the degradation of cortisol to cortisone, it also helps to convert 11β-hydroxyandrogens into 11-ketotestosreone, the typical teleost androgen, with more masculinizing potency than testosterone (Piferrer et al, 1993). In contrast, in the Japanese flounder, it was suggested that cortisol suppressed gonadal aromatase (cyp19a1a) expression by blocking the cAMP response element located in the cyp19a1a promoter .…”
Section: Discussionmentioning
confidence: 99%
“…In the pejerrey, cortisol interacts with the glucocorticoid response element in the promoter of the 11β-hydroxysteroid dehydrogenase type 2 (hsd11β2) gene, a key enzyme that is shared between the glucocorticoid and androgen pathways, increasing its expression. This led Fernandino et al, (2012Fernandino et al, ( , 2013 to suggest that while increased hsd11β2 expression contributes to the degradation of cortisol to cortisone, it also helps to convert 11β-hydroxyandrogens into 11-ketotestosreone, the typical teleost androgen, with more masculinizing potency than testosterone (Piferrer et al, 1993). In contrast, in the Japanese flounder, it was suggested that cortisol suppressed gonadal aromatase (cyp19a1a) expression by blocking the cAMP response element located in the cyp19a1a promoter .…”
Section: Discussionmentioning
confidence: 99%
“…We also noted while performing artificial fertilization that all 1‐year‐old YY males ( n  = 11) had abundant milt production compared to 36.4% (eight of 22) in XY males (unpublished observations), suggesting that the former may attain sexual maturation earlier than the latter. Studies including mRNA quantification of genes involved in amh signaling (such as amhy , amha , and amhr2 ) and measurement of androgens and stress hormones, which are related to sex determination in pejerrey (Fernandino, Hattori, Kishi, Strüssmann, & Somoza, 2012; Hattori, Fernandino, et al., 2009), will be conducted for comparison of thermal sensitivity between XY and YY fish. Similar studies should examine whether amhy has any role in the onset of puberty in this species that could explain the early maturation observed in YY fish.…”
Section: Discussionmentioning
confidence: 99%
“…In fish, 11␤-HSD2 is also important in testicular androgen activation and sex determination (197) by catalyzing conversion of 11␤-hydroxytestosterone to active 11-keto-testosterone (470).…”
Section: F 11␤-hsd1 Regulationmentioning
confidence: 99%
“…Both 11␤-HSD1 and 11␤-HSD2 are expressed in the adult male reproductive tract, although there are substantial species differences (4,369). In fish testis, 11␤-HSD2 plays a glucocorticoid-independent role, converting 11␤-hydroxytestosterone to 11-ketotestosterone, a major fish androgen important in fertility and sex determination (197,324,573). 11␤-HSD2 is absent from the chicken testis (351).…”
Section: The Reproductive Systemmentioning
confidence: 99%